The associations of dietary exposure to selected food additives with dietary patterns and overweight - Irit Atary-Sheetryt; Danit Rivkah Shahar; Sivan Ben-Avraham; Kerem Avital; Sigal Tepper (PLoS ONE, 2026)
Background The global rise in obesity correlates with increased consumption of ultra-processed foods, which often contain various food additives. The impact of these additives on obesity remains underexplored. Objectives This study aimed to assess the association between the intake of food additives and overweight and obesity, and their correlation with diet quality. Methods Data were derived from the Tel-Hai cohort, which includes 924 adults aged 19–65 years from diverse ethnic backgrounds. Participants provided demographic information, quality of life, and physical activity data through a questionnaire. Dietary intake was assessed using a 116-item Food Frequency Questionnaire (FFQ). Body Mass Index (BMI) was calculated based on self-reported height and weight, categorizing participants into normal weight (BMI ≤ 25) and excess weight (BMI > 25) groups. The study quantified participants’ exposure to food additives from the FFQ, focusing on consumption of ultra-processed foods containing additives such as preservatives, colorants, and artificial sweeteners. Adherence to the Mediterranean diet [MD] was assessed using a 9-point score, divided into 3 levels of adherence. Results Analysis of data from 924 respondents revealed that 622 individuals (67.3% of the total) were at normal weight, while 302 (32.7%) were overweight or obese. Overweight/obese individuals consumed more preservatives (sorbates and nitrites), stabilizers (carrageenan and sulfates), and artificial sweeteners (acesulfame K, cyclamate, and aspartame) (p < 0.05). Lower adherence to the MD corresponded with significantly higher consumption of these additives. Additionally, demographic variables such as age and ethnicity correlated with higher additive intake and obesity rates. Conclusion Although food additive consumption did not exceed safety limits, its association with obesity highlights a potential public health concern. The findings advocate for dietary guidelines that consider the broader implications of ultra-processed products beyond caloric and nutrient content.